Impacts of environmental factors on fine root lifespan - McCormack, M. Luke; Guo, Dali (Frontiers in Plant Science, 2014)
The lifespan of fast-cycling roots is a critical parameter determining root turnover, a large flux of plant carbon into soil, and is a biological feature regulating the capacity of a plant to capture soil water and nutrients via root-age-related physiological processes. While the importance of root lifespan to whole-plant and ecosystem processes is increasingly recognized, robust descriptions of this dynamic process and its response to changes in climatic and edaphic factors are lacking. Here we synthesize available information and propose testable hypotheses using conceptual models to describe how changes in temperature, water, nitrogen and phosphorus availability impact fine root lifespan within a species. Each model is based on intrinsic responses including root physiological activity and alteration of carbohydrate allocation at the whole-plant level as well as extrinsic factors including mycorrhizal fungi and pressure from pathogens, herbivores, and other microbes. Simplifying interactions among these factors, we propose three general principles describing fine root responses to complex environmental gradients. First, increases in a factor that strongly constrains plant growth (temperature, water, nitrogen, or phosphorus) should result in increased fine root lifespan. Second, increases in a factor that exceeds plant demand or tolerance should result in decreased lifespan. Third, as multiple factors interact fine root responses should be determined by the most dominant factor controlling plant growth. Moving forward, field experiments should determine which types of species (e.g. coarse vs. fine rooted, obligate vs. facultative mycotrophs) will express greater plasticity in response to environmental gradients while ecosystem models may begin to incorporate more detailed descriptions of root lifespan and turnover. Together these efforts will improve quantitative understanding of root dynamics and help to identify areas where future research should be focused.